2021
DOI: 10.1007/s11695-021-05271-7
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y Gastric Bypass Downregulates Angiotensin-Converting Enzyme 2 (ACE2) Gene Expression in Subcutaneous White Adipose Tissue: A Putative Protective Mechanism Against Severe COVID-19

Abstract: Graphical Abstract The angiotensin-converting enzyme 2 (ACE2) is the receptor for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It is highly expressed in adipose tissue, possibly associated with progression to severe coronavirus disease 2019 (COVID-19) in obese subjects. We searched the Gene Expression Omnibus (GEO) and reanalyzed the GSE59034 containing microarray data from subcutaneous white adipose tissue (sWAT) biopsies from 16 women before and 2 years after RYGB, and 16 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Weight loss achieved by bariatric surgery determines a significant reduction in adipose tissue volume, and also downregulates ACE 2 gene expression in the subcutaneous adipose tissue, which might also constitute a putative protective mechanism against severe COVID-19. Roux-en-Y gastric bypass was demonstrated to positively impact numerous comorbidities obesity-related (often linked to poorer COVID-19 outcomes), resulting independently associated with a reduced risk of mechanical ventilation and death in obese patients with COVID-19 (43).…”
Section: Obesity and Covid-19 Pathogenesismentioning
confidence: 99%
“…Weight loss achieved by bariatric surgery determines a significant reduction in adipose tissue volume, and also downregulates ACE 2 gene expression in the subcutaneous adipose tissue, which might also constitute a putative protective mechanism against severe COVID-19. Roux-en-Y gastric bypass was demonstrated to positively impact numerous comorbidities obesity-related (often linked to poorer COVID-19 outcomes), resulting independently associated with a reduced risk of mechanical ventilation and death in obese patients with COVID-19 (43).…”
Section: Obesity and Covid-19 Pathogenesismentioning
confidence: 99%
“…Besides dietary interventions, bariatric surgery, such as Roux-en-Y gastric bypass (RYGB), represents an additional effective intervention tool to reduce adipose tissue volume. Therefore, RYGB is currently considered as a potential strategy to reduce COVID-19 risk of infection, especially in patients suffering from severe obesity [ 45 ]. Indeed, analysis on publicly available transcriptomic datasets (GSE59034) of subcutaneous white adipose tissue (sWAT) biopsies from 16 women before and 2 years after RYGB revealed that ACE2 gene expression is down-regulated by RYGB in this tissue.…”
Section: Influence Of Obesity and Diet In Adipose Tissue Ace2 Levels Evidence From Studies Conducted In Humansmentioning
confidence: 99%
“…Indeed, analysis on publicly available transcriptomic datasets (GSE59034) of subcutaneous white adipose tissue (sWAT) biopsies from 16 women before and 2 years after RYGB revealed that ACE2 gene expression is down-regulated by RYGB in this tissue. It is worth noting that the Ace2 gene expression in these patients resulted even lower than that found in subcutaneous adipose tissue of subjects that had never been obese [ 45 ].…”
Section: Influence Of Obesity and Diet In Adipose Tissue Ace2 Levels Evidence From Studies Conducted In Humansmentioning
confidence: 99%
“…In another U.S. study that conducted a multivariate analysis, a prior history of metabolic surgery was associated with a lower hospital admission rate compared with control patients with obesity. Intriguingly, it is noted that Roux-en-Y gastric bypass downregulates ACE2 gene expression in subcutaneous adipose tissue [ 40 ], which might act as a protective mechanism against COVID-19 infection.…”
Section: The Role Of Bariatric and Metabolic Surgeries During The Cov...mentioning
confidence: 99%
“…In this analysis, the mean presurgical BMI was 44.5±6.8 kg/m In another U.S. study that conducted a multivariate analysis, a prior history of metabolic surgery was associated with a lower hospital admission rate compared with control patients with obesity. Intriguingly, it is noted that Roux-en-Y gastric bypass downregulates ACE2 gene expression in subcutaneous adipose tissue[40], which might act as a protective mechanism against COVID-19 infection.Although bariatric surgery is being postponed due to COVID-19, the American Society for Metabolic and Bariatric Surgery (ASMBS) recently released a statement regarding metabolic and bariatric surgery during the COVID-19 pandemic. The society claims that metabolic and bariatric surgeries should be resumed when it is safe, and it disagrees with the concept that the surgery should be postponed until the pandemic is over.…”
mentioning
confidence: 99%